Retributive Justice in Ancient Mesopotamian Law: Institutional Foundations of Punishment in the Code of Hammurabi - Roberth Kurniawan Ruslak Hammar; Bernardus Horokubun; Imanuel Inriyanto Ruslak Hammar (Cendekiawan Indonesia Timur, 2026)
Ancient Mesopotamia occupies a central position in the history of written law, particularly through the Code of Hammurabi, one of the earliest and most systematic legal collections of the ancient world. This article examines the concept of retributive justice in Babylonian legal thought and analyzes the institutional foundations of punishment reflected in the Code of Hammurabi. Using normative legal research with historical and conceptual approaches, the study explores how punishment was constructed, legitimized, and applied within the social and political order of ancient Babylon. The findings show that the Code of Hammurabi embodied the principle of lex talionis, emphasizing proportionality between offense and punishment as a core expression of retributive justice. However, punishment was not merely a moral response to wrongdoing; it was also embedded in institutional mechanisms involving courts, royal administration, and the king’s authority as the ultimate source of legal legitimacy. The study further reveals that the application of punishment was shaped by Babylonian social hierarchy, where legal consequences varied according to the status of offenders and victims. Historically, the Code of Hammurabi contributed to the development of criminal law thought by providing an early foundation for proportional punishment, legal codification, and the relationship between law, authority, and social order.